Teachers' perspectives on factors which facilitated and hindered the implementation of curriculum 2005 (C2005) in the general education and training (GET) band in one district of the Eastern Cape Province in South Africa - Cishe, Elphinah Nomabandla (2011)
The study investigated teachers' perspectives on factors which facilitated and hindered the implementation of Curriculum 2005 in the General Education and Training (GET) Band in one district of the Eastern Cape Province in South Africa. Curriculum 2005 was the new curriculum underpinned by the outcomes-based education. It was introduced in South Africa as a way of moving away from the apartheid system of education, which was based on racial lines, and to offer a uniform system of education. The implementation of Curriculum 2005 was a process which had to follow a certain time-frame, starting from Grade 1 in 1998, with the intention that it would have been introduced in all grades by 2005. When in the year 2000 it became clear that the suggested time-frame could not be achieved, the then Minister of Education, Asmal, commissioned a review process which culminated in the Revised National Curriculum Statement (RNCS) introduced in 2004, and finally the National Curriculum Statement (NCS), which was introduced for the first time in 2006, in the Further Education and Training (FET) Band.